2022
DOI: 10.1093/rheumatology/keac407
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of a Hispanic lupus nephritis cohort from Mexico

Abstract: Objectives To characterize the clinical presentation and outcomes of lupus nephritis (LN) in a Hispanic cohort from Mexico. Methods We studied 440 subjects with systemic lupus erythematosus and biopsy-proven LN followed for >36 months. We obtained demographic, clinical, laboratory, histopathological, and treatment variables. All outcomes were analysed by survival analysis and included response to therapy, renal relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Lupus nephritis (LN), the most worrisome manifestation of SLE, is significantly more frequent in them (24)(25)(26)(27). This coincides with our study, which included the Hispanic mestizo population, where we observed that the most frequent identified phenotype was renal.…”
Section: N Discussionsupporting
confidence: 87%
“…Lupus nephritis (LN), the most worrisome manifestation of SLE, is significantly more frequent in them (24)(25)(26)(27). This coincides with our study, which included the Hispanic mestizo population, where we observed that the most frequent identified phenotype was renal.…”
Section: N Discussionsupporting
confidence: 87%
“…Assessment of some immunological markers in Iraqi patients with Systemic Lupus Erythematosus and Lupus Nephritis (LN) showed increased levels of blood urea (BU) and creatinine (Cr), in groups of patients (SLE with LN, SLE without LN) in comparison with controls (14) . A recent study proved that one of the factors associated with loss kidney function was doubled their serum creatinine (15) . SLErelated hepatitis (LH) is a separate entity that affects 3-8% of SLE patients and is characterized by subclinical and slight elevations of liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 49 , 50 In contrast, patients with partial response, usually defined as stable kidney function and a 50% decrease in proteinuria, still have a 50% probability of progressing to kidney failure, either by an increased risk for renal relapses or by persistent kidney inflammatory activity. 46 , 51 , 52 , 53 …”
Section: The Post-therapy Kidney Biopsy: Histological Response Therap...mentioning
confidence: 99%